Noise immunity of QAM-OFDM signal reception using soft-decision demodulation in the presence of narrowband interference - A. A. Paramonov; V. V. Chu (Российский технологический журнал, 2024)
Objectives. The aim of this paper is to study the noise immunity of digital information transmission in systems with orthogonal frequency division multiplexing (OFDM) and quadrature amplitude modulation (QAM) of subcarriers in the presence of narrowband interference. As a way of managing this interference, the paper studies the use of a demodulator with soft outputs and subsequent decoding of the convolutional code and low-density paritycheck (LDPC) code used in the system.Methods. The results presented in the article were obtained using statistical radio engineering, mathematical statistics, encoding theory, and computer modeling.Results. The paper presents a simple method for calculating soft bit estimates in the M-point signal QAM demodulator, where M is an even power of two. A considerable amount of numerical results were obtained which show the dependence of the transmitted information bit error rate on M, as well as on the signal-to-noise ratio, signal-to-narrowband interference, and code rates.Conclusions. It can be concluded from the above results that the use of encoding with soft demodulator decisions significantly improves the noise immunity of OFDM signal reception, and enables narrowband interference to be managed efficiently. LDPC encoding is superior to convolutional encoding in increasing the noise immunity of OFDM signal reception both in the absence and in the presence of narrowband interference. Along with the use in QAM-OFDM systems, the proposed simple method for demodulating QAM signals with soft decisions can be used in any wireless communication system using M-position QAM signals, where M is 2 to an even power.